THE IMPACT OF MANAGEMENT INFORMATION SYSTEM ON UNIVERSITIES’ MANAGERIAL DECISION-MAKING (Journal of the Management Sciences, 2024)
Management is often saddled with decision – making in planning, directing, controlling coordinating, financing and staffing functions. Information is a critical factor for effective and efficient managerial decision-making in universities Quality decisions, its efficient communication and effective implementation are the live wire of every organization like the Universities. Quality managerial decision is critical and vital to success and achievement of the Universities goals and activities. Quality Information is the bedrock, fulcrum and the veritable resource of the universities’ quality managerial decision. It is often the output of Universities’ Management Information system (UMIS). Management Information System is the state-of-the-art Information technology tool for gathering, processing and churning good information for managerial decisions. This study examines the effect or influence of universities management information technology on managerial decision – making in Universities. It investigates factors that influences information gathering, processing, communication, utilization and the flow of effective information. It also assesses the influences of information flow on managerial decision-making in Universities. The results revealed great and numerous invaluable impact the adoption and application of UMIS has on universities’ management decision-making. It offers very high efficiency and unparallel effectiveness in managerial decision-making in universities due to quality information from the UMIS. The result especially depicted better results, improved performance, highly increased productivity, reduced data risk and insecurity, enhanced viability and values, reduced operational headaches and cost, enhanced goodwill and maximized control and flawless attainment of Universities’ goals and aspirations with growing scalability and as well successful churning out readymade manpower for the industries and workplaces in Nigeria and across the globe. The major drawbacks are cost, technical barrier, professional demand. power, data accuracy and security breaches, etc.
Keywords: MIS, Information, Decision-Making, Managerial Decision